Antioxidant activity of amino acid sodium and potassium salts in vegetable oils at frying temperatures. (1st April 2022) - Hwang, Hong‐Sik; Winkler‐Moser, Jill K.; Liu, Sean X.
Abstract: Previous studies reported that several amino acids had strong antioxidant activity in vegetable oils under frying conditions. In this study, amino acids were converted to their sodium or potassium salts, and a heating study was conducted with 5.5 mM amino acid salts in soybean oil (SBO) at 180°C. Sodium salts of amino acids including alanine, phenylalanine, and proline and disodium glutamate had significantly stronger antioxidant activity than the corresponding amino acids, and potassium salts had stronger antioxidant activity than sodium salts. Potassium salts of alanine and phenylalanine more effectively retained tocopherols in SBO than the corresponding amino acids during heating. Phenylalanine potassium salt had stronger antioxidant activity than phenylalanine in other vegetable oils including olive, high oleic soybean, canola, avocado, and corn oils. Phenylalanine potassium salt at 5.5 mM more effectively prevented oil oxidation than tert ‐butyl hydroquinone, a synthetic antioxidant, at its legal concentration limit (0.02%) indicating its feasibility as a new antioxidant for frying.